Dupuytren's disease susceptibility gene, EPDR1, is involved in myofibroblast contractility. Issue 2 (August 2016) - Staats, Kim A.; Wu, Timothy; Gan, Bing S.; O'Gorman, David B.; Ophoff, Roel A.
Highlights: All three EPDR1 transcripts are detected in affected Dupuytren's tissue. Dupuytren's tissue contracts more in the FPCL paradigm. Knockdown of EPDR1 moderately attenuates late stage of contraction rate in FPCL. Abstract: Background: Dupuytren's Disease is a common disorder of the connective tissue characterized by progressive and irreversible fibroblastic proliferation affecting the palmar fascia. Progressive flexion deformity appears over several months or years and although usually painless, it can result in a serious handicap causing loss of manual dexterity. There is no cure for the disease and the etiology is largely unknown. A genome-wide association study of Dupuytren's Disease identified nine susceptibility loci with the strongest genetic signal located in an intron of EPDR1, the gene encoding the Ependymin Related 1 protein. Objective: Here, we investigate the role of EPDR1 in Dupuytren's Disease. Methods: We research the role of EPDR1 by assessing gene expression in patient tissue and by gene silencing in fibroblast-populated collagen lattice (FPCL) assay, which is used as an in vitro model of Dupuytren's contractures. Results: The three alternative transcripts produced by the EPDR1 gene are all detected in affected Dupuytren's tissue and control unaffected palmar fascia tissue. Dupuytren's tissue also contracts more in the FPCL paradigm. Dicer-substrate RNA-mediated knockdown of EPDR1 results in moderate late stage attenuation of contraction rate in FPCL, implying a role in matrix contraction. Conclusion: Our results suggest functional involvement of EPDR1 in the etiology of Dupuytren's Disease.